2014
DOI: 10.1097/id.0000000000000061
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Radiographic, and Esthetic Evaluation of Immediately Loaded Laser Microtextured Implants Placed into Fresh Extraction Sockets in the Anterior Maxilla

Abstract: Immediate implants with a laser microtextured surface restored at the day of surgery, may be considered as a predictable procedure in terms of implant survival and hard and soft tissue remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 46 publications
3
22
0
Order By: Relevance
“…Review of the titles and abstracts resulted in 22 articles identified as full‐text articles, and seven were excluded for the following reasons: follow‐up <12 months; 44 , 45 redundant studies; 32 LMS design not only in implant neck; 21 , 46 performed with additional surgeries such as hard 47 or soft tissue 48 augmentation. Finally, 15 eligible articles 21‐31,33‐36 were included in this study. The characteristics of the included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Review of the titles and abstracts resulted in 22 articles identified as full‐text articles, and seven were excluded for the following reasons: follow‐up <12 months; 44 , 45 redundant studies; 32 LMS design not only in implant neck; 21 , 46 performed with additional surgeries such as hard 47 or soft tissue 48 augmentation. Finally, 15 eligible articles 21‐31,33‐36 were included in this study. The characteristics of the included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Three articles are RCTs 30 , 31 , 33 and six are cohort studies 27‐29,34‐36 . Six case series 21–26 observing implants with LMS collars without controls were also included to evaluate the overall performances of the LMS design. All articles were published from 2009 to 2016.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations